D19 final plan for using and disseminating knowledge - Oliveira, Vítor (2008)
This document presents the Final Plan for Using and Disseminating Knowledge acquired throughout the development of the CYCLOPS project as deliverable D19. It includes a description of the main achievements in disseminating knowledge, and the consortium and each participant’s plans for the exploitation of the results for the consortium as a whole, or for individual participants or groups of participants. It updates the Plan for Using and Disseminating Knowledge that was presented as Deliverable D4 and describes the final dissemination plan of the CYCLOPS project. This deliverable provides a strategy aimed at addressing various target communities in order to achieve the project dissemination and exploitation goals. After an update of the dissemination instruments employed, the deliverable focuses on the description of the dissemination activities carried out. In addition to the normal dissemination and exploitation of the work through scientific journals and professional bodies, Civil Protection Community will be specifically targeted for dissemination of the CYCLOPS deliverables, and their future exploitation of the results. Other written deliverables focus on presenting dissemination activities in specific subject areas. In particular deliverable D17 reports “the results of the dissemination of EGEE towards the Civil Protection community, and about the coordination between the EGEE and CYCLOPS activities”, deliverable D18 focuses on “collecting the CYCLOPS project results for dissemination towards different interested audiences such as Grid communities, other Civil protection agencies, but also national and international initiative and projects, SMEs, etc.” and deliverable D20 that reports “the extent to which actors beyond the research community have been involved to help spread awareness and to explore the wider societal implications of the proposed work.